Identify digital indicators to predict the performance of some basic skills by indicating some physical abilities in football players under the age of 15 - Lournik , youcef; khadar , khaled (sports creativity, 2025)
this study aims at finding the values of quantity of some physical abilities that takes part and participate in some basic skills of football, where the sample was selected in the intended manner of football players under the age of 15 affiliated with sports clubs active in the second regional association Batna in Ben Srour , the researchers used the descriptive method. The final results shows that there is a statistical relation between the physical abilities studied and some basic skills of football, in which these abilities contribute largely to the accuracy of this techniques, this study led to the deduction of four predictive equations that determines the accuracy of performances in relation to the physical abilities covered by the study